ANALISIS PENDAPATAN USAHATANI KELAPA SAWIT POLA SWADAYA DI KABUPATEN ROKAN HILIR - Mardianis Mardianis; Novia Dewi; Rosnita Rosnita (Fakultas Pertanian, Universitas Riau, 2023)
The oil palm farming of independent farmers plays an important role as a source of income in Rokan Hilir Regency. This study aims to analyze the income of independent oil palm smallholders in Rokan Hilir. This study used survey methods and interviews with key persons and independent farmers oil palm. The location of this research was determined purposively. A sampling of representative areas using multistage area sampling. The number of respondents was 93 persons. The research data taken consisted of primary data and secondary data. Data analysis used to use farming analysis: production costs, revenue, income. The result of the study was that the average total income 0f independent palm oil in Rokan Hilir was IDR 11,434,710.28 per year per hectare or IDR 37,085,765.71 per year per cultivated area. Meanwhile. The average total production cost incurred is IDR 166,888.65 per year per hectare or IDR 1,671,519.76 per year per cultivated area. So that an average net income of IDR 9,124,415.74 per year is obtained per hectare or IDR 30,696,704.21 per year per cultivated area.